ANALISIS KEPUASAN MASYARARAKAT TERHADAP PELAYANAN KESEHATAN RUMAH SAKIT HARAPAN INSANI - Ulianto Ulianto; Ede Surya Darmawan (Yayasan Pendidikan Medika Indonesia, 2022)
Background: The qualified health services are based on satisfaction level on common population and excellent service based on standards ethics professional codes, fulfilled exceed the patient's expectations and satisfaction. Hospitals must be working effective and efficient.. The center view of health care provider is no longer the caregiver, but the corner of services has been patient-oriented. In order to reach patient satisfaction, it is necessary to pay attention to things that play an important role in determining the perception of patient quality, including facilities, the role of physicians and nurses. Subjects and methods: The respondents was randomly selected by the Non Probability Sampling method. This study using a questionnaire containing the community satisfaction index on 14 measuring values ​​of hospital performance, the descriptive statistics used to quantitative analysing. Results: From 150 questionnaires, the average value of patient satisfaction with outpatient services at Harapan Insani Hospital was 87,614. and for admitted patients was 85,208, and for the price get an average value of 52,25. Conclusion: The respondents expressed their satisfaction at Harapan Insani Hospital, Pangkalan Bun. From the respondents, there is feedback for the problem of the rate of admitted patients due to the using of branded drugs, it makes problem for unit cost calculation. This analysis met solution to improve the performance of Harapan Insani Hospital, to fulfilled expectation of health care user in the Kotawaringin Barat region.